ART in Indonesia: A Current Review of Ethics - cinta ayu abutari (Journal of Global Pharma Technology, 2019)
Currently, Assisted Reproductive Technology (ART) programs such as intrauterine insemination (IUI) and in vitro fertilization (IVF) are developed in Indonesia. As a religious country, the implementation of ART programs raises a variety of ethical issues and religion reactions such as sperm or oocyte donor was haram, sperm from the deceased husband, a sinful masturbation, surrogate mother was Zina, gender selection by human, man assumption as God to decide which embryo be transferred and to create life. Some specific religious organizations provide statements regarding this matter based on scriptural studies and the opinions of their respective religious leaders. Confucianism allows sex selection, while other religions refuse. Hindu and Buddhist allow all ART program, while Catholic declare rejection to all ART program. Islam allows ART programs, without sperm and oocyte donor or surrogate mother. This difference in views is mediated by government regulations that support ART programs but are still limited by legal marital status. The state provides government rules on the implementation of the ART program in Indonesia, although every spouse is allowed to follow their beliefs. In conclusion, ART programs were allowed by most of the religions in Indonesia, as long as not involve the third party as the donor.